WEIGHTLIFTING SPORTS SPECIAL PREPARATORU EXERCISES OF BARBEL LIFTING FOR INCREASING WEIGHTLIFTING CLEAN EXERCISE RESULTS - Čupriks, Leonīds; Getmančuks, Edgars; Čuprika, Aleksandra; Zuša, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Improvement of weightlifters technical skills and special physical qualities involves use of different instrumental control methods, which are necessary for obtaining biomechanically accurate quantitative parameters of the athlete's movement structure. Such control, using biomechanical methods, allows us to substantiate the parameters of the exercise techniques for competitions and to identify factors that affect the effectiveness of the movement activity. Our research aim was to evaluate the effect of non-standard barbell lifting exercises on results of weightlifting competition. The study subjects were healthy 15 weightlifters. The assessment of dynamic parameters was done before and after the set of exercises by using non-standard weightlifting bar using FITRO Dyne Premium (Slovakia). The maximum muscle strength dynamics was performed by the REV 9000 Technogym (Italy) isokinetic dynamometer, along with the registration of muscle biopotentials (EMG). Data was analyzed using Excel statistics 3.1. After ascertaining experiment with a set of exercises with an non-standard barbell lifting on clean exercise, the dynamic parameters of the controlled barbell lifting on weightlifting clean exercise (standard performance) were improved.